Are distinctive risk indicators associated with different stages of caries in children? A cross-sectional study - Maria Grazia Cagetti; Giovanna Congiu; Fabio Cocco; Gianfranco Meloni; Silvana Sale; Guglielmo Campus (BMC, 2016)
Abstract Background Actual caries figures emphasize the need to identify the risk indicators involved in the disease's development. The hypothesis that certain risk indicators might affect the dynamic evolution of the caries process was assessed; to clarify this premise, a cross-sectional survey was performed in school children. Methods A total of 390 subjects aged 6-8 years old were randomly selected. Caries was assessed, and the subjects were stratified as follows: i) highest caries score; ii) most prevalent caries score; and iii) number of affected teeth. Parents/guardians completed a questionnaire regarding vital statistics, socio-economic indicators, dietary habits, oral hygiene habits and oral health behaviours. Results Caries was detected in 42.31% of the subjects. Maternal nationality, parental education level, use of a sweetened pacifier at night, intake of lactose-free milk and toothbrushing frequency were statistically significant associated (p < 0.05) with subjects stratified according to the highest caries score. Parental educational level, maternal occupational status and use of a sweetened pacifier at night were associated (p < 0.05) with affected children stratified according to the most prevalent caries score. Maternal educational level and intake of lactose-free milk were associated with subjects with moderate caries stages compared to being caries-free (p = 0.01 and p = 0.02, respectively). Maternal nationality (p < 0.01) and toothbrushing frequency (p = 0.01) were associated with subjects affected by extensive lesions compared to caries-free children. In subjects affected by initial lesions as the most prevalent figure, gender (male) and paternal occupation status (unemployed) were statistically significant associated (p = 0.03 and p = 0.04, respectively) compared to those affected by highest prevalence of extensive caries lesions. In children with the highest prevalence of moderate caries lesions, maternal education level (p < 0.01), paternal occupational status (p = 0.03) and use of a sweetened pacifier at night (p < 0.01) were statistically significantly associated. Conclusions Maternal nationality, maternal low level of education, intake of lactose-free milk and low toothbrushing frequency were involved in the change from caries-free status to different caries stages. Gender, paternal unemployment, maternal low educational level and use of a sweetened pacifier were correlated with caries progression, showing how distinctive risk indicators were associated with different caries stages.